Requirement of Functional Ethylene-Insensitive 2 Gene for Efficient Resistance of Arabidopsis to Infection by Botrytis cinerea - Thomma, Bart P.H.J. (American Society of Plant Physiologists, 1999)
Inoculation of wild-type Arabidopsis plants with the fungus Alternaria brassicicola results in systemic induction of genes encoding a plant defensin (PDF1.2), a basic chitinase (PR-3), and an acidic hevein-like protein (PR-4). Pathogen-induced induction of these three genes is almost completely abolished in the ethylene-insensitive Arabidopsis mutant ein2-1. This indicates that a functional ethylene signal transduction component (EIN2) is required in this response. The ein2-1 mutants were found to be markedly more susceptible than wild-type plants to infection by two different strains of the gray mold fungus Botrytis cinerea. In contrast, no increased fungal colonization of ein2-1 mutants was observed after challenge with avirulent strains of either Peronospora parasitica or A. brassicicola. Our data support the conclusion that ethylene-controlled responses play a role in resistance of Arabidopsis to some but not all types of pathogens.